Collaborative Teams: Teachers, Parents, and Allied Health Professionals Supporting Students With Autism Spectrum Disorder in Mainstream Australian Schools. Issue 2 (11th December 2020) - Vlcek, Samantha; Somerton, Michelle; Rayner, Christopher
Abstract: The unique traits and behaviours of students with autism spectrum disorder (ASD) often present a range of barriers to their educational experiences and development. The present study investigated collaborative partnerships between 3 stakeholders that often support students with ASD: teachers, parents, and allied health professionals (AHPs). With current literature on collaboration between teachers, parents, and AHPs involved in the education of students with ASD predominantly relating to specific skill or knowledge acquisition, there was an insufficient understanding of 'collaborative processes' and the factors that benefit or limit effective practice. In the present study, the researchers explored the experiences, processes, and opinions of parents, teachers, and AHPs supporting students with ASD in mainstream Australian primary schools. A total of 129 responses were recorded (41 teachers, 44 parents, and 44 AHPs) through an online survey, and thematic data analysis was used to qualitatively interpret the open-ended questions. The findings highlight the current opportunities and challenges faced by key stakeholders in this important process.